FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KALA II LAMA - Destariyani, Elvi (JURNAL MEDIA KESEHATAN, 2016)
Kalla II long is one of the direct causes of the high maternal mortality rate inthe world. In dr. M Yunus in 2011 of women giving birth in 1047 of 196 (18.72%) of themothers had prolonged second stage of labor, and in 2012 of 1060 women giving birth as215 (20.28%) mothers had prolonged second stage. The research objective is to determinewhat are the factors associated with the incidence of prolonged second stage of labor inthe CI Space Hospital Midwifery. Dr. M. Yunus Bengkulu city.This study design was adescriptive cross sectional analytic approach. The population is all women giving birth inhospitals M.Yunus Bengkulu in 2012 as many as 1060 people. 290 samples were taken bypurposive sampling. Collecting data using secondary data.The results show most womengiving birth (51.4%) multiparous, most maternal (54.1%) aged less than 20 years andmore than 35 years, almost half of women giving birth (42.8%) fetal weight more than4000 grams, and the maternal part (50%) experienced a prolonged second stage, and therewas a significant association between parity with prolonged second stage, there was asignificant association between maternal age with prolonged second stage, there was asignificant association between fetal weight with time II time.Under these conditions it isexpected that the hospitals Dr.M. Yunus care delivery can minimize the risk of morbidityand maternal and infant mortality by improving the quality and quantity of theproposition, infrastructure and human resources that are reliable and competent.